Characterizing viscoelastic properties of human melanoma tissue using Prony series - Park, Seungman; Chien, Anna L.; Brown, Isabelle D.; Chen, Jingchun (Frontiers in Bioengineering and Biotechnology, 2023)
Melanoma is the most invasive and deadly skin cancer, which causes most of the deaths from skin cancer. It has been demonstrated that the mechanical properties of tumor tissue are significantly altered. However, data about characterizing the mechanical properties of in vivo melanoma tissue is extremely scarce. In addition, the viscoelastic or viscous properties of melanoma tissue are rarely reported. In this study, we measured and quantitated the viscoelastic properties of human melanoma tissues, based on the stress relaxation test, using the indentation-based mechanical analyzer that we developed previously. The melanoma tissues from 8 patients of different ages (57 – 95), genders (male and female), races (White and Asian), and sites (nose, arm, shoulder, and chest) were excised and tested. Results showed that the elastic property (i.e., shear modulus) of melanoma tissue was elevated compared to normal tissue, while the viscous property (i.e., relaxation time) was reduced. Moreover, the tissue thickness had a significant impact on the viscoelastic properties, probably due to the amount of adipose layer. Our findings provide new insight into the significance of viscous properties as well as elastic properties, which may be implicated in disease state and progression.